2021
DOI: 10.1021/acsanm.1c01177
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Rich La2O3 Nanoparticles with Antioxidant Activity for Human Keratinocytes

Abstract: A deficiency in the human antioxidant system to scavenge free radicals results in mounting oxidative stress, causing various pathological conditions including immune system constraints. To support an underperforming antioxidant system and regulate homeostatic function, efficient and biocompatible reactive oxygen species (ROS) scavengers may be employed. At present, metal oxide-based antioxidants nanoparticles are of fundamental interest because of their smart surface property tailoring. A spray precipitation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
(83 reference statements)
1
9
0
Order By: Relevance
“…The La2O3 nanostructure synthesised by the spray precipitation method for biological applications was reported by Rehman et al [182]. Mostly, an irregular or thick plate-like morphology was observed in the SEM imaging (Figure 16a).…”
Section: Oxygen-deficient Lanthanum Oxidementioning
confidence: 57%
See 4 more Smart Citations
“…The La2O3 nanostructure synthesised by the spray precipitation method for biological applications was reported by Rehman et al [182]. Mostly, an irregular or thick plate-like morphology was observed in the SEM imaging (Figure 16a).…”
Section: Oxygen-deficient Lanthanum Oxidementioning
confidence: 57%
“…A lower dye degradation (~44%) was recorded in the presence of La 2 O 3 NPs compared to the P25-only assay (~96%) shown in Figure 16c. A confocal microscopy study showed the cellular (HaCaT cell line) internalisation of NPs (Figure 16d) [182]. The cytotoxicity data revealed the biocompatible nature of the nanostructure, even at a higher concentration (500 mg L −1 ) with reference to ZnO (Figure 16e).…”
Section: Oxygen-deficient Lanthanum Oxidementioning
confidence: 94%
See 3 more Smart Citations